(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The phenomenon of domestic violence has spread widely and rapidly among an unlimited group of people in different societies, as the world has faced many forms of violence throughout the ages, and many have defined violence as behavior that leads to harm to others, whether this harm is physical or psychological. , or verbal.In this context, this research aimed to identify the types of deviance, learn about the manifestations of development in adolescence, the influence of the family on the adolescent, and how to reduce domestic violence directed against adolescents because of its dangerous consequences for individuals, the family, and society, which requires researchers to , scholars, and workers in the social field in particular, intensify efforts to address this phenomenon and reduce its risks. The descriptive analytical approach was adopted, after which some recommendations and proposals were made to alleviate the phenomenon of domestic violence against adolescents. The research reached results, the most important of which is that the concept of domestic violence as a social phenomenon is broad and exists in most societies alike, and is not due to just one cause, and this is the essence of the social phenomenon, as there are multiple factors and reasons that lead to the emergence of such negative phenomena in some societies, which is A certain reflection of social relations, its distinct character of expressing and influencing these relations, and its special role and purpose in the historical social practice of humanity